ANALISIS PEMILIHAN BIJI KOPI BERKUALITAS DENGAN MENERAPKAN METODE VIKOR - Rini Ade Willana; Sajaratud Dur; Fibri Rakhmawati (LPPM Universitas Bina Bangsa, 2024)
Indonesia is the fourth largest coffe producer in the world. One of the centers of coffee cultivation in Indonesia is Central Aceh, whichis located in Gayo Highlands, which cultivates Arabica coffee. The problems that occur at this time raise question from coffee farmer groups about determining the quality of coffee beans to be distributed. The purpose of this research is to determine the quality of the coffee beans that will be distributed by applying the VIKOR method. VIKOR is ranking method using a multi-criteria ranking index based on the proximity of the ideal solution and determining the ranking of the existing samples. There are four alternatives used by Gayo1, Gayo2,Gayo3, and P88. There area six criteria, namely water content, dirt content, seed aroma, seed color, seed size, and pests. After calculating the VIKOR method which show the lowestindex value, namely 0 is Gayo3 as the first rabk, value 0,065 is P88 second rank, value 0,085 is Gayo2 rank thind, and value 1 is for Gayo1